2019
DOI: 10.1002/celc.201801688
|View full text |Cite
|
Sign up to set email alerts
|

B‐Doped Fe/N/C Porous Catalyst for High‐Performance Oxygen Reduction in Anion‐Exchange Membrane Fuel Cells

Abstract: The development of high-performance non-precious metal catalysts for the oxygen reduction reaction (ORR) as an alternative to platinum-based counterparts in fuel cells is highly desirable but challenging. In this study, a facile approach for preparing a porous boron-bearing Fe/N/C catalyst by pyrolysis was reported. The obtained FeCNB-900 with a high surface area (784 m 2 g À 1 ) favored a 4e À -reduction pathway for ORR, with a half-wave potential of~0.86 V vs. RHE and high stability in 0.1 M KOH. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 61 publications
2
12
0
Order By: Relevance
“…By adjusting the electronic structure and improving the electronic conductivity, large atomic radius S atom doping of the carbon matrix has been carried out to elevate ORR activity effectively. 10–16 Zhou and Sun et al synthesized an S-doped Fe–N–C SAC for the first time with a high surface area and S-doping level to realize excellent ORR activity for a high kinetic current of 23 A g −1 at 0.80 V in 0.1 M H 2 SO 4 solution. 17 After that, Tang, 18 Li, 19 Wang, 20 and others 16,21–23 have realized S-doped Fe–N–C SACs for ORR with high half-wave potentials, firm stability, high methanol tolerance and successful application in Zn–air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…By adjusting the electronic structure and improving the electronic conductivity, large atomic radius S atom doping of the carbon matrix has been carried out to elevate ORR activity effectively. 10–16 Zhou and Sun et al synthesized an S-doped Fe–N–C SAC for the first time with a high surface area and S-doping level to realize excellent ORR activity for a high kinetic current of 23 A g −1 at 0.80 V in 0.1 M H 2 SO 4 solution. 17 After that, Tang, 18 Li, 19 Wang, 20 and others 16,21–23 have realized S-doped Fe–N–C SACs for ORR with high half-wave potentials, firm stability, high methanol tolerance and successful application in Zn–air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ORR performance of Fe–N–C was further improved by the introduction of B elements. As shown in Figure a, it can be concluded that B doping in the Fe–N–C system affects the charge balance of the adjacent carbon and improves the turnover frequency of Fe sites, which promotes the ORR activity. ,, …”
Section: Resultsmentioning
confidence: 96%
“…This result was attributed to the introduction of a three-dimensional crosslinked structure of MFs, which brought a larger specific surface 4a, it can be concluded that B doping in the Fe−N−C system affects the charge balance of the adjacent carbon and improves the turnover frequency of Fe sites, which promotes the ORR activity. 45,57,58 For the purpose of further evaluating the influence of Fe, B, and N codoping effect on the ORR in acidic conditions, the electrocatalytic activity of all samples was also investigated in an O 2 -saturated 0.1 M HClO 4 aqueous solution. Obviously, Fe−B−N−C had the most positive oxygen reduction potential compared to other samples in the CV curves (Figure S12a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the ORR on the B-doped pyrolyzed Fe−N−C system is unable to produce hydrogen peroxide in both associative and dissociative pathways, the ORR on this system follows the 4e-reduction pathway, which is also in direct agreement with the experimental results. 16,17…”
Section: Discussionmentioning
confidence: 99%